Psychiatric nurses’ experiences of patient aggression - Kołodziej, Kinga; Lickiewicz , Jakub; Jelonek, Ewa; Mlocek, Magdalena; Murzyn, Małgorzata; Dudek, Małgorzata (Nursing in the 21st Century, 2021)
PSYCHIATRIC NURSES’ EXPERIENCES OF PATIENT AGGRESSION Introduction. Employees of psychiatric hospitals, especially the closed wards, experience aggression almost every day. Aggression in psychiatry is a particularly complex problem and is the subject of numerous studies. In this field of medicine, aggressive behavior of hospitalized patients is treated by the staff as an understandable, but undesirable component of work. The personnel’s confrontation with the above phenomenon is treated as a part of professional duties determined by the place of their performance. Aim. The aim of the study was to determine the frequency of aggressive behaviors in patients and to assess their impact on nursing staff employed in psychiatric departments. Material and methods. The study was conducted in 2017 in a group of nursing staff employed at the Clinical Hospital Dr Joseph Babinski in Cracow. The number of 196 nurses participated in the study. It was a cross-sectional study and consisted of one stage – the completion of the research tool by participants. Results. The results showed that 94.39% of the respondents were a victim of aggressive behavior on the part of patients. The most common verbal aggression experienced by the respondents were: verbal taunts, the use of vulgar words by the hospitalized, using offensive nicknames and shouting at the staff, while physical were: destroying hospital property, attempting to hit, throwing objects and destroying own belongings. Conclusions. The scale of the phenomenon of experiencing aggression on the part of patients in the group of nurses working in psychiatric departments indicates the need to conduct research into this subject and also to conduct staff training taking into account coping with aggressive behavior of patients.